Mobile learning environment design requirements for Quran readers with down syndrome / Norhaslina Kamarulzaman - Norhaslina , Kamarulzaman (2018)
Educational technology refers to the process of teaching or tools that help teachers make teaching and learning more effective. The advances of computer technology in the era of education is aimed to make sure that the information revolution will affect students’ lives more deeply and thoroughly. Hence, it is very important to study and understand the real needs of users to enable these technology-based learning aids to achieve that goal. Besides that, people with special needs, especially learning disabilities, are in dire need of assistance in terms of science and technology in their daily lives. Therefore, in a learning environment, it is important to produce a learning app that fits the real needs of students in their learning environment. Based on the literature review, there is a lack of information on learning environments for people with learning disabilities, especially in Islamic studies. In Malaysia, the Down syndrome (DS) population is increasing and requires special attention, especially in their education later on. Furthermore, there is a lack of learning apps that suit the learning environment of DS students. Based on these problems, this study aims to i) identify factors associated with the learning process and the learning environment of children with DS; ii) obtain the appropriate method to recite the Quran (targeted to recognise hijaiyah letters) for children with DS; iii) propose a model to assist students with DS in the learning process that uses their learning strengths; and iv) evaluate the acceptance levels against the M-learning prototype app among the DS children in the process of recognising the hijaiyah letters. This research design was developed according to a method adapted from the User Centred Design process (UCD). The data collection in this study was conducted using the Fuzzy Delphi Method (FDM) that includes analysing relevant documentations, doing expert interviews, observation and studies using questionnaires to acquire requirement needs and good factors in a learning environment for DS students. Meanwhile, the Human Computer Interaction (HCI) guidelines are used to understand the learning environment for children. Data collection was obtained from interview sessions with 12 teachers, observation sessions with 13 students with DS, and surveys with 30 participants; whereby the students’ skill of learning is taken into consideration for the purposes of user requirement needs. The findings of this research have highlighted studies on the identification of characters of DS students, their environment of learning, and requirements of learning technology aids in terms of DS students’ requirements in their learning environment. Through this study, characteristics of DS students and their requirement needs in the learning process can be understood more clearly. A Down Syndrome Enhanced Requirements Learning (DSERL) model was suggested to help the software developer or programmer to create an app or learning software that are most appropriate for DS students. This model is based on the environment of Mobile Learning (M-learning), the basic elements of M-Learning Characteristic Framework by Martin and Ertzberger (2013), and Learning environment and Learning Style of DS as the outcome of the data collection in this study. In addition, this study also contributed to the Muslim community by developing an app for “Jawi” alphabets recognised as a prototype for DSERL; whereby it can be seen as an alternative that provides equal opportunity for children with DS to recite the Quran just like normal children do.